Teacher Performance Supervision in International Elementary Schools: Principal Challenges - Triyadi, Triyadi; Yusuf, Munawir; Subagya, Subagya (Universitas Pendidikan Indonesia Kampus Serang, 2024)
Supervision conducted by school principals is an important element in improving the effectiveness of teaching and learning in schools. Through the supervision process, principals provide support, feedback and guidance that are essential for teachers' professional development. This collaborative approach to supervision that focuses on improving the quality of learning plays an important role in achieving the educational goals of the school. This study aims to describe and analyze the challenges faced by principals in conducting teacher performance supervision in international primary schools. This type of research is qualitative research with a narrative approach. Data were collected through observation, interviews, and document analysis of seven principals of international primary schools in Surakarta. The results of this study showed that principals in international primary schools face several challenges, including (1) the time of supervision; (2) communication; (3) the consistency of assessment; (4) perceptual differences; and (5) the skill for conducting supervision. This research provides an in-depth insight into the complexity of the principals’ challenges in conducting teacher performance supervision in international primary schools. This research is expected to help understand the dynamics of supervision in the international primary schools, which can be applied more broadly in improving teacher professionalism in the academic process.